Marine heatwaves disrupt the culling of Crown-of-Thorns Starfish on the Great Barrier Reef - Kailash Cook; Christina Skinner; Yves-Marie Bozec; Peter J Mumby (Coral Reefs, 2026)
Crown-of-Thorns Starfish (CoTS) predation poses an enduring threat to coral health on the Great Barrier Reef (GBR), driving substantial investment in research and control efforts. However, how CoTS respond to heat stress in situ remains uncertain, limiting our ability to optimise control efforts. We analysed 33 years of CoTS control records, including pre-culling surveys (manta tows) and cull data, with satellite-derived thermal stress metrics to investigate how heat stress influences CoTS detections and culling effectiveness patterns across the GBR. CoTS detections on pre-culling surveys declined significantly with cumulative heat stress, decreasing by 22% per °C-week increase in Degree Heating Weeks (DHW) to a maximum absolute decrease of 95% at 12°C-weeks. Cull data showed 9–14% fewer CoTS culled per dive per °C-week depending on size. These patterns underpin a seasonal response: CoTS culling efficiency peaks in winter and declines in summer, with deeper and longer summer troughs under higher annual heat stress. Culling is triggered when pre-culling surveys meet thresholds for CoTS feeding scars or abundance. We find the false-positive rate, cases where no CoTS are later encountered, is higher (50%) when culls are triggered by scars than by sightings (36%), indicating scars are a less reliable indicator of CoTS presence. Finally, while coral and CoTS populations often exhibit a dynamic balance on controlled reefs, this equilibrium deteriorates when heat stress exceeds ~6 °C-weeks, leading to accelerated coral loss compounded by CoTS presence. This highlights the need for adaptive management strategies that incorporate seasonal and thermal shifts in CoTS behaviour, especially as ocean warming intensifies.

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Engineering, Ecological and Social Monitoring of the Largest Underwater Sculpture in the World at John Brewer Reef, Australia - Adam Smith; Al Jayson Songcuan; Nathan Cook; Rachelle Brown; Kailash Cook; Reuben Richardson (Journal of Marine Science and Engineering, 2022)
The largest underwater sculpture in the world, the ‘Coral Greenhouse’ by artist Jason deCaires Taylor, was commissioned by the Museum of Underwater Art and installed at John Brewer Reef, Australia, in December 2019. The planning process required certified engineering design drawings associated with design life, durability and suitability of materials, and baseline ecological surveys. Following approval, the operational phase required annual monitoring of substrate, ecology, social values, and marine debris. We geo-referenced three permanent transects and designed a before/after rapid monitoring assessment of substrate, fish, and invertebrates. Substrate surveys indicated 11% concrete and 89% sand. Fish surveys indicated significant increases of diversity and abundance, with 12 species and 65 individuals recorded in 2018 compared to 46 species and 365 individuals recorded in 2022. Macroinvertebrate species maintained no significant trends in abundance, species richness, and diversity with respect to time between 2018 and 2022. We monitored coral restoration and natural recruitment at the site, measuring aesthetics, survivorship of planted corals, and coral recruitment. Of 131 corals transplanted in March 2020, survivorship was 100% at 1 month, 92% at 6 months, and 91.6% at 12 months. Hard and soft corals were recruited to the structure at a density of 8.35 hard corals/m2 and 10.9 soft corals/m2 over 26 months.

Evaluation of a CXCR4 antagonist in a xenograft mouse model of inflammatory breast cancer - Balraj Singh; Kendra R. Cook; Cecilia Martin; Eugene H. Huang; Kailash Mosalpuria; Savitri Krishnamurthy; Massimo Cristofanilli; Anthony Lucci (Clinical & Experimental Metastasis, 2010)